Phospholipid Synthesis in Escherichia coli Infected with T4 Bacteriophages - Furrow, Marjorie H. (1968)
After infection of Escherichia coli with T4 phage, phospholipid synthesis continued but at a reduced rate. The same phospholipid components were synthesized as in uninfected cells; however, the relative rates of (32)P(i) incorporation into phosphatidylglycerol (PG) and phosphatidylethanolamine (PE) were altered. This alteration was most pronounced during the first 10 min after infection. Under these conditions, the isotope incorporated into PG equaled or exceeded that found in PG from uninfected cells. Chloramphenicol (CM) added before, but not 5 min after, infection inhibited the relative increase in PG synthesis, and CM added at different times after infection indicated that a protein synthesized between 3 and 6 min was required for this change to occur. Supplies of exogenous l-serine or l-α-glycerol-P failed to affect the relative rates of (32)P(i) incorporation into PG and PE by infected or uninfected cells. Phospholipid synthesis was somewhat higher after infection with T4rII mutants than after infection with wild-type phage. After infection with these mutants or several amber mutants, the relative synthesis of PG and PE was characteristic of T4r(+)-infected cells. The phospholipid synthesized after infection did not rapidly turn over, but infection accelerated the loss of PG synthesized prior to infection.